A prospective study of treatment of distal femur fractures with locking condylar plate - Bhanu Rekha, Y.; Brahmananda Reddy, N. (International Journal of Research in Orthopaedics, 2017)
Background: Multiple implants are available to treat distal femoral fractures. The recent addition is the locking plate contoured to the distal femur with combiholes in the proximal portion. Though it is established that locking plates offer higher stability than the previous implants like dynamic compression screw or condylar buttress plate, some studies showed higher incidence of delayed union. We evaluated 30 type A and type C distal femoral fractures treated with locking condylar plate in our institutes. Methods: We conducted a prospective study on 30 consecutive patients with fractures of distal femur operated with locking condylar plate from December, 2015 to February, 2017. Patients were regularly followed up with x-rays and clinical examination. At the end of one year follow-up, patients were evaluated with Pritchett score. Results: Fracture union was seen in all patients. Union was faster in type A fractures than in type C intra articular fractures. 67% of patients achieved excellent to good grading according to Pritchett rating system. Conclusions: Locking condylar plate is effective in treating distal femoral fractures with minimal complications.